Thermal and mechanical optimization of nano-foams for sprayed insulation. (20th March 2019) - Stazi, F.; Urlietti, C.; Di Perna, C.; Chiappini, G.; Rossi, M.; Tittarelli, F.
Highlights: Nanoclay and silica dioxide in polyurethane foams. Explored different percentages of nano/microparticles and foam densities. Multidisciplinary evaluation of thermo-hygrometric and mechanical performance. 4 wt% nanoclay in high density foams achieved the best performance. Abstract: This study investigates the effects of the addition of two different types of particles on morphological, thermo-hygrometric and mechanical properties of thermal insulating sprayed polyurethane foams. Platelet nanoclay and spherical silicon dioxide microparticles were poured into two different foams with a density of 15 Kg/m 3 and 30 Kg/m 3, respectively used for cavity walls infill and external insulation layers. Nanoclay particles were dispersed into the polyol through a sonication technique followed by a mechanical mixing into the isocyanate, whereas silica dioxide microparticles (aerogel) were mixed mechanically into the polyol then added to isocyanate. Results showed that the introduction of small amounts (2% and 4% in weight) of nanoparticles and microparticles significantly enhances both thermal and mechanical properties of the foams. Among the low-density foams, the best thermal performance was recorded by 4 wt% nanoclay sample with a reduction of the conductance of about 9% whereas the best mechanical performance was recorded by 4 wt% aerogel sample with an increase of the tensile modulus of about 300%. However even the 4wt% nanoclay addition significantly enhanced the outcomes of the mechanical tests. Also among the high-density foams, the best thermal and mechanical compromise was achieved by the one containing 4% in weight of nanoclay, that showed a reduction of the conductance of about 7% and an increase of the tensile modulus of about 180%. This latter sample resulted to be the most performing among all the foams.